Performance enhancement by aperture averaging in terrestrial and satellite free space optical links. Issue 3 (1st June 2016) - Viswanath, Anjitha; Gopal, Pooja; Jain, Virander Kumar; Kar, Subrat
Abstract : In this study, characterisation of atmospheric turbulence in terrestrial and satellite free space optical links is presented. For these links, usage of aperture averaging for performance enhancement is discussed. It is observed that aperture averaging is effective only in terrestrial links and satellite downlink. In the case of uplink, aperture averaging is non‐practical due to large value of spatial coherence radius. On evaluating the link performance for different intensity modulation schemes, the performance of 8‐pulse position modulation (PPM) scheme is found to be the best followed by 8‐differential PPM (DPPM), 2 × 4‐pulse amplitude and position modulation (PAPM), on–off keying (OOK) and 2 × 4‐differential amplitude PPM (DAPPM) schemes at low turbulence conditions. However, the performance of 8‐PPM, 8‐DPPM and 2 × 4‐PAPM schemes degrade more than that of OOK and 2 × 4‐DAPPM schemes, with increase in ground level turbulence and zenith angle implying cross‐over of error curves for some schemes. The computed results on the effect of aperture averaging for a point‐to‐point terrestrial link shows that it is most effective for 8‐PPM, followed by 8‐DPPM, 2 × 4‐PAPM, OOK and 2 × 4‐DAPPM.